2007
DOI: 10.2113/gsecongeo.102.7.1321
|View full text |Cite
|
Sign up to set email alerts
|

Structural Control on the Dikulushi Cu-Ag Deposit, Katanga, Democratic Republic of Congo

Abstract: The Dikulushi Cu-Ag deposit is located in the Kundelungu Plateau region in the southeast Katanga province of the Democratic Republic of Congo. The Kundelungu Plateau is a triangular-shaped area to the north of the Lufilian arc, which contains part of the Central African copperbelt, the largest known sediment-hosted copper province in the world. The Lufilian arc and the Kundelungu Plateau comprise Neoproterozoic sedimentary rocks of the Katanga Supergroup that attain an overall thickness of more than 7,000 m. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
(25 reference statements)
1
18
0
Order By: Relevance
“…Taylor, 1984;De Roo, 1988;Baudemont and Fedorowich, 1996;Broadbent et al, 1998;Yigit et al, 2003;Jolley et al, 2004;Haest et al, 2007), and shown by the examples of vein-type mineralization in this paper. At camp and deposit scales, such structural controls are represented by strain localization (shear strain and dilation), the formation of linear structures (faults, shear zones and fractures) and the reactivation of pre-existing structures, which in turn influence fluid flow and mineral precipitation.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Taylor, 1984;De Roo, 1988;Baudemont and Fedorowich, 1996;Broadbent et al, 1998;Yigit et al, 2003;Jolley et al, 2004;Haest et al, 2007), and shown by the examples of vein-type mineralization in this paper. At camp and deposit scales, such structural controls are represented by strain localization (shear strain and dilation), the formation of linear structures (faults, shear zones and fractures) and the reactivation of pre-existing structures, which in turn influence fluid flow and mineral precipitation.…”
Section: Discussionmentioning
confidence: 52%
“…fault, thrust-fracture or folds) include: (1) the Silvermines PbeZn deposit in Ireland (Taylor, 1984); (2) Mount Carbine WeSn deposit, Queensland, Australia (De Roo, 1988); (3) Dominique-Peter U deposit, Saskatchewan, Canada (Baudemont and Fedorowich, 1996); (4) Century Zn deposit, Northwest Queensland, Australia (Broadbent et al, 1998); (5) Carlin-type Au deposit in the Gold Bar District, Nevada (Yigit et al, 2003). (6) Au deposits in the Witwatersrand basin (Jolley et al, 2004) and Bendigo, Australia (Schaubs and Wilson, 2002); (7) the CueAg deposits of D. R. Congo (Haest et al, 2007). Studying and understanding of key structural factors controlling mineralization in an area can lead to the determination of exploration targets and the discovery of ore bodies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1000 m thick tabular fluvio‐deltaic red arkoses (Redbeds) can be found, defined as the Inkisi Subgroup in West Congo (Alvarez et al , 1995), the Aruwimi Group in the Lindi–Ubangi region (Verbeek, 1970) and the Upper Kundelungu (Ku3) in the foreland of the Katanga belt. For the latter, it has been described as ‘Plateaux’ Subgroup (Lepersonne, 1974a, 1974b; Dumont et al , 1997; Dumont & Hanon, 2000; Cailteux et al , 2005; Batumike et al , 2006) and recently renamed ‘Biano’ Subgroup by Batumike et al (2007) and Haest et al (2007). Ar‐Ar dating of detritical muscovites form this unit by Master et al (2005) gave a maximum age of 573 Ma (terminal Edicarian), supporting the idea that it has been deposited in the foreland of the Lufilian orogen.…”
Section: Stratigraphic Evolutionmentioning
confidence: 95%
“…The primary stratiform Cu-Co sulfide mineralization is early syn-diagenetic (Dewaele et al, 2006;El Desouky et al, 2010;Muchez et al, 2008) and occurred around 820 Ma (Selley et al, 2005) and/or after ~750 Ma (Hitzman et al, 2005). Later mineralization events took place before or during the pan-African Lufilian folding (Cailteux et al, 2005;DecrĂ©e et al, 2011;DecrĂ©e et al, 2014;Dewaele et al, 2006;El Desouky et al, 2009;Haest and Muchez, 2011;Haest et al, 2007;Haest et al, 2009;Kampunzu et al, 2009). In these primary deposits, carrollite (CuCo 2 S 4 ), siegenite ((Ni,Co) 3 S 4 ) and linnaeite (Co 2+ Co 3+ 2 S 4 ) are the most abundant primary cobalt ore minerals.…”
Section: Geological Settingmentioning
confidence: 99%